Fenomena childfree marriage oleh publik figur - Sa'diyah, Halimatus (Maliki Interdisciplinary Journal, 2024)
The phenomenon of childfree marriage has become a controversial issue that is increasingly known and understood by the Indonesian people. Popularized by social media activists or so-called public figures who give statements that they decide not to have children due to their own reasons, especially the assumption that the presence of children gives great responsibility and the decision becomes a freedom for each couple. The purpose of the study provides an explanation of several reasons behind childfree marriage carried out by public figures along with views from netizens and Islamic law on the childfree decision. The research method used is sociological juridical based on youtube analysis with a theological approach, namely the Qur'an and hadith. The results showed that many factors were used as reasons for public figures to do childfree That is from the interests of himself and his family, accompanied by several views stating the pros and cons of both netizens and Islamic law about the decision. The majority of scholars do not support childfree because it is contrary to the purpose of marriage law whereas contemporary scholars argue that childfree is not prohibited by Islamic law because there is no proposition governing it that can be energized by Imam Al Ghazali's opinion on the permissibility of childfree caused by endangering life, soul, reason, offspring, property and religion.